The Influence of Employee Engagement on Job Satisfaction of Agency Employees National Narcotics Provincial South Kalimantan - Jean Abner Evabras; Fanlia Prima Jaya (Hut Publication Business and Management, 2025)
HR refers to all individuals involved in the operation of an organization, from the lowest level of management to the highest level. Job satisfaction is a positive emotional state that arises from the assessment of one's work. This includes various aspects such as salary, working conditions, relationships with coworkers, and opportunities for development and promotion. Job satisfaction and employee engagement are two important aspects in human resource management that are directly related to job satisfaction. BNNP South Kalimantan must increase awareness of the threat of narcotics. The high level of drug abuse requires employees to have high employee engagement for optimal performance and dedication. This study aims to determine the effect of employee engagement on the job satisfaction of employees of the National Narcotics Agency of South Kalimantan Province. The type of research conducted in this study is causal associative research using a quantitative approach. The sample in this study was taken based on the Non-probability sampling technique with a total sample of 38 permanent employees of the National Narcotics Agency of South Kalimantan Province. The analysis method in this study uses Simple linear regression analysis to test or find out the relationship between one independent variable with the dependent variable with the help of SPSS 22. Based on the results of the study, it shows that the Employee Engagement variable has a significant effect on the Job Satisfaction variable. Based on the results of the analysis and discussion in the previous chapter, the researcher draws the following conclusions: Employee engagement has a significant effect on job satisfaction in employees of the National Narcotics Agency of South Kalimantan Province